Quantitative assessment of three Shorea species at Kenaboi Forest Reserve, Negeri Sembilan - Hasnan, Mohamad Hasrol Shah (2016)
Shorea acuminata, Shorea parvifoliaand Shorea leprosula are main Dipterocarps species in Malaysia and South East Asia countries. The species are fast growing Shorea species and highly utilised in buildings and construction. Two of the species except S. parvifolia is not listed in IUCN Red List of Threatened Species. Thus, it is important to carry out in situ and ex situ conservation. One of the ex situ effort is Taungya system. A total of 99 trees were selected using transact line in six plots. Height, dbh, volume and basal area were assessed in this study.S. leprosula outperformed S. parvifolia and S. acuminata in terms of dbh, height, basal area and volume. Mean dbh for S. leprosula is 53.41 followed by S. parvifolia (45.45 cm) and S. acuminata (40.59 cm). In terms of tree height, S. leprosula is 30.62 m followed by S. parvifolia (27.83 m) and S. acuminata (26.75 m). For basal area, S. leprosula is 0.23 m2 followed by S. parvifolia (0.17 m2) and S. acuminata (0.14 m2). Lastly, for volume; S. leprosula is 3.01 m3 followed by S. parvifolia (2.18 m3) and S. acuminata(1.66 m3). Based on mean dbh and height showed S. leprosula outperformed the other two species however, with the conversion of basal area and volumeto the one hectare basis, the ranking as follows: S. parvifolia>S. acuminata>S. leprosula. However, the result should be taken carefully due to norm that most/least number of samples influenced the results.